D'arisun AR: Inovasi Media Augmented Reality Berbasis Etnomatematika Sunda untuk Pembelajaran Barisan Aritmatika di SD - Mahmud Masulin; Huri Suhendri; Silvia Septhiani (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
Have you ever imagined third-grade elementary school students learning arithmetic sequences while observing Mega Mendung batik motifs or playing congklak? That is what D'arisun AR attempts to realizean Augmented Reality-based learning medium that integrates Sundanese ethnomathematics. This preliminary study was conducted in three public elementary schools in Tapos District, Depok, because students' mathematics scores were still around 66-70, below the minimum passing grade of 75. Interviews with teachers and students revealed that instruction remained conventional, rarely used technology, and had not yet touched upon local culture. In fact, students were very enthusiastic about visual learning, games, and things familiar to their daily lives. This article presents how D'arisun AR emerges as an answer: combining AR, batik motifs, and traditional games to make number patterns more concrete, enjoyable, and meaningful. The study recommends further development using the 4-D model so that mathematics learning in elementary schools is no longer feared, but eagerly anticipated.